Audiovisual emotional processing and neurocognitive functioning in patients with depression - Doose-Grünefeld, Sophie; Eickhoff, Simon B.; Müller, Veronika I. (Frontiers in Integrative Neuroscience, 2015)
Alterations in the processing of emotional stimuli (e.g. facial expressions, prosody, music) have repeatedly been reported in patients with major depression. Such impairments may result from the likewise prevalent executive deficits in these patients. However, studies investigating this relationship are rare. Moreover, most studies to date have only assessed impairments in unimodal emotional processing, whereas in real life, emotions are primarily conveyed through more than just one sensory channel. The current study therefore aimed at investigating multi-modal emotional processing in patients with depression and to assess the relationship between emotional and neurocognitive impairments. 41 patients suffering from major depression and 41 never-depressed healthy controls participated in an audiovisual (faces-sounds) emotional integration paradigm as well as a neurocognitive test battery. Our results showed that depressed patients were specifically impaired in the processing of positive auditory stimuli as they rated faces significantly more fearful when presented with happy than with neutral sounds. Such an effect was absent in controls. Findings in emotional processing in patients did not correlate with BDI-scores. Furthermore, neurocognitive findings revealed significant group differences for two of the tests. The effects found in audiovisual emotional processing, however, did not correlate with performance in the neurocognitive tests. In summary, our results underline the diversity of impairments going along with depression and indicate that deficits found for unimodal emotional processing cannot trivially be generalized to deficits in a multi-modal setting. The mechanisms of impairments therefore might be far more complex than previously thought. Our findings furthermore contradict the assumption that emotional processing deficits in major depression are associated with impaired attention or inhibitory functioning.